(untitled) (Mustansiria Dental Journal, 2024)
Background: An injury to both primary and permanent teeth and the supporting structures is one of the most common dental problems seen in children. The extent of injury may vary from mild chipping of enamel to sever maxillofacial injury. The aim of this study was to find out the prevalence of traumatized anterior teeth among primary school children. Materials and methods: This study is a cross-sectional survey was carried out through clinical examination of anterior teeth among 720, 6-13 year old children enrolled in primary public schools of tikrit city. The prevalence of traumatized anterior teeth was studied in relation to age, gender, type of injury in addition to the cause of fracture. Recording and diagnosis of dental fracture were assessed according to Garcia-Godoy classification. Results: Males were more affected than females with odds ratio was 2.53 and statistically was significant. The higher prevalence of dental trauma was recorded among the age 10-11 year old. The permanent maxillary central incisors were the most frequent injured tooth and the most frequent type of fracture was the Class II Enamel-Dentine, fracture without pulp exposure. Fall and playing were the most frequent causes of dental injury. Conclusion: data of the present study clearly show the need for dental health education of children and their parents, so prevention programs are needed to improve the dental health of Iraqi children.